Long Noncoding RNA LINC01554 as a Novel Biomarker for Diagnosis and Prognosis Prediction of Epithelial Ovarian Cancer. (10th August 2021) - Luo, Ting; Jiang, Yan; Yang, Jing
Abstract : Objective . This study was aimed at exploring the diagnostic and prognostic value of long noncoding RNA LINC01554 (LINC01554) in epithelial ovarian cancer (EOC) patients. Patients and Methods . The expressions of LINC01554 in 161 EOC patients were analyzed using RT-PCR. The area under the ROC curve (AUC) was used to estimate the effectiveness of LINC01554 for prediction. The chi-square test was performed to explore the association between LINC01554 expressions and clinical characteristics in EOC patients. Kaplan-Meier assays were conducted for the examination of the influence of LINC01554 expression on the overall survival of EOC patients. Multivariate analyses were carried out to further determine prognostic values of LINC01554 expression in EOC patients. Results . LINC01554 expressions were strongly downregulated in EOC specimens compared with matched nontumor specimens (p < 0.01 ). Importantly, LINC01554 provided a high diagnostic performance for the detection of EOC specimens (AUC = 0.7827 ; p < 0.001 ). Low expression of LINC01554 was distinctly associated with the FIGO stage (p = 0.034 ) and distant metastasis (p = 0.007 ). The assays of survival data (five years) revealed that the 5-year overall survival of the low LINC01554 expression group was distinctly shorter than that of the high LINC01554 expression group (p = 0.0017 ). Finally, in the multivariate Cox model, LINC01554 expression (RR = 2.863, 95% CI: 1.185-4.421, p = 0.014 ) was demonstrated to be an independent prognostic factor for overall survival of EOC patients. Conclusions . Our findings suggested that LINC01554 is an important EOC-related lncRNA, providing a potential diagnostic, prognostic biomarker and therapeutic target for EOC patients.